Regional Dermoscopic Features of Plaque Psoriasis Vulgaris on (the body, face and scalp) - Massoud, Aya; Al-Hamamy, Hayder (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Background Dermoscopy is a non-invasive tool used for the visualization of deeper structures in the skin. It aids in the diagnosis of multiple skin diseases. The early uses of dermoscopy were for pigmented skin lesions. Nowadays, it is used for inflammatory, infectious, scalp and nail diseases. Objectives To describe the dermoscopic features of chronic plaque psoriasis on the body, face and scalp. Patients and Methods The study is an observational cross-sectional study performed over one year at Baghdad Dermatology Teaching Center. Dermoscopic features were noted and analyzed in classic plaque psoriasis on the body, the scalp and the face. Variables dermoscopically studied were; 1.The pattern of vessels distribution. 2. The shape of vessels. 3. Background color. 4. Scale distribution 5. Scale color. Results In body psoriasis the most common vascular pattern was regular (52.1%) and the shape of vessels was dots and globules (90.2%), the background was mainly pink (63%), scales were mainly diffusely distributed (34.9%) and white in color (46.7%). On the scalp the presence of vessels were less evident than body, no vessels were seen in (55%) and when found they were mainly regular in (18.4%) and the main shape was dots and globules (46%), the background as on the body was mainly pink in color in (79.4%), scales were diffuse in (56.3%) and white in (42.5%) of cases. In face and scalp psoriasis blood vessels were less than body psoriasis, no vessels were found in (53.6%) and when found they were mainly patchy (28.6%) and the main shape was dots and globules in (46.4%), the background was pink and red equally and scales were mainly diffuse (42.8%) and white/yellow (46.5%). Conclusions Regularly distributed dots and globules with pink background and diffuse white scales were the most common findings in plaque psoriasis on the body, face and scalp. Vessels were more conspicuous in plaque body psoriasis than face and scalp psoriasis. No vessels could be found in 54% of scalp and face psoriasis. So the absence of vessels does not rule out the diagnosis of psoriasis.